Effects of desensitizing products on the reduction of pain sensitivity caused by in-office tooth bleaching: a 24-week follow-up (Journal of Applied Oral Science, 2021)
Objective: To clinically assess the effect of desensitizing gels and dentifrices on the reduction in pain sensitivity and color variation during tooth bleaching. Methodology: A total of 108 volunteers were randomly separated into the following groups of n=12: GT/S-glycerine and thickener/sucralose; NF/S-potassium nitrate and sodium fluoride/sucralose; NA/S-potassium nitrate and arginine/sucralose; GT/AC-glycerine and thickener/arginine and calcium carbonate; NF/AC-potassium nitrate and sodium fluoride/arginine and calcium carbonate; NA/AC-potassium nitrate and arginine/arginine and calcium carbonate; GT/PN-glycerine and thickener/potassium nitrate; NF/PN-potassium nitrate and sodium fluoride/potassium nitrate; and NA/PN-potassium nitrate and arginine/potassium nitrate. Sensitivity was assessed with the numerical analogue scale, and color variation (ΔE) was measured with a spectrophotometer. The sensitivity values obtained were subjected to a multivariate analysis of variance (MANOVA) and color variation values were subjected to a randomized analysis of variance (p<0.05). Results: The NF/AC, NA/AC, NF/PN, and NA/PN groups presented lower sensitivity values and reduced sensitivity compared to those of the other groups throughout the clinical sessions. None of the groups showed sensitivity at the 24-week assessment. Statistically, no significant difference were observed in the color values among the groups four weeks after the beginning of bleaching (p=0.074). Additionally, the color assessment of all groups was statistically similar four weeks (p=0.084) and 24 weeks (p=0.118) after the beginning. Conclusion: Our results indicate that adding NF/S, NA/S, NF/AC, and NA/AC desensitizers to tooth bleaching protocols reduces pain sensitivity without affecting its effectiveness.